2022
DOI: 10.3233/bmr-200176
|View full text |Cite
|
Sign up to set email alerts
|

Tilt and mobility of the hip girdle in the sagittal and frontal planes in healthy subjects aged 19–30 years

Abstract: BACKGROUND: Disturbances in pelvic girdle tilt can cause compensatory changes affecting postural dysfunctions, and can lead to hip and groin strain changes and back pain. However, we still have no clear information on the normative values of pelvic girdle tilt and mobility. OBJECTIVE: The study aimed to (1) evaluate the position and mobility of the pelvic girdle in the sagittal and frontal planes in asymptomatic adults aged 19–30, (2) evaluate the possible variation of results according to gender and to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The values for ePT and eST found in females and males are within the range of reference values described by other authors 1,13,23) , so we can assume that there were no particular anomalies here. We found moderate to strong correlations between the investigated pelvic parameters external pelvic tilt and external sacral tilt.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The values for ePT and eST found in females and males are within the range of reference values described by other authors 1,13,23) , so we can assume that there were no particular anomalies here. We found moderate to strong correlations between the investigated pelvic parameters external pelvic tilt and external sacral tilt.…”
Section: Discussionsupporting
confidence: 88%
“…The shape of the spine is a decisive factor in the analysis and evaluation of human posture. The alignment of the pelvis in the sagittal plane plays an important role in posture and movement 1) , as the anchoring of the sacrum in the pelvic bones means that a forward tilt of the pelvis also biomechanically leads to a forward tilt of the sacrum 2,3) . This results in an increased lordosis of the lumbar spine [4][5][6] , which in turn can lead to an increased thoracic kyphosis as compensation 7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the research, the authors tried to maintain restrictive test conditions to maintain the reliability and repeatability of measurements. Previous studies have shown that measurements using the Duometer show high repeatability under the conditions of tests conducted by an experienced examiner (Bibrowicz and Bibrowicz, 2011a;Bibrowicz et al, 2022).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The exclusion criteria were: (1) any injuries during the 3 months directly preceding the study, and (2) any surgeries that could affect the muscle tone and early termination of the study. Subjects were divided into subgroups according to the body type determined by their BMi (underweight, normal weight, overweight and obese), the value of the pelvic tilt in the sagittal plane (anterior pelvic tilt, neutral pelvis, posterior pelvic tilt) [24], and sex. Among the subjects, 85 had a BMi ratio within the normal range, 54 were underweight and 40 were overweight or obese [25].…”
Section: Participantsmentioning
confidence: 99%